2015
DOI: 10.1073/pnas.1505914112
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of apicomplexan calcium-dependent protein kinases

Abstract: Calcium-dependent protein kinases (CDPKs) comprise the major group of Ca 2+ -regulated kinases in plants and protists. It has long been assumed that CDPKs are activated, like other Ca 2+ -regulated kinases, by derepression of the kinase domain (KD). However, we found that removal of the autoinhibitory domain from Toxoplasma gondii CDPK1 is not sufficient for kinase activation. From a library of heavy chain-only antibody fragments (VHHs), we isolated an antibody (1B7) that binds TgCDPK1 in a conformation-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…CDPK1 was detected using the alpaca-derived nanobody 1B7 (Ingram et al, 2015). Rabbit polyclonal sera were used to detect MyoA (Frénal et al, 2014), PLP1 (Kafsack et al, 2009) and ACT1 (Dobrowolski et al, 1997).…”
Section: Methods and Resourcesmentioning
confidence: 99%
“…CDPK1 was detected using the alpaca-derived nanobody 1B7 (Ingram et al, 2015). Rabbit polyclonal sera were used to detect MyoA (Frénal et al, 2014), PLP1 (Kafsack et al, 2009) and ACT1 (Dobrowolski et al, 1997).…”
Section: Methods and Resourcesmentioning
confidence: 99%
“…Ingram et al . () identified an allosteric mechanism relying on the interaction between the end of the variable N‐terminal domain and the CaMLD. Although this N‐terminal region is not conserved in plant CDPKs, especially the F39 residue playing a critical role in TgCDPK1, other contact sites might exist to mediate a similar regulatory mechanism in some plant CDPKs.…”
Section: Structure and Regulation Of Cdpks/crksmentioning
confidence: 97%
“…Based on this activation model, it was postulated that truncated CDPKs lacking both JD and CaMLD should be constitutively active, independently of calcium. Although this has proven to be true for many plant CDPKs (Harmon et al ., ; Harper et al ., ; Sheen, ; Boudsocq et al ., ), some truncated variants were totally inactive, for example TgCDPK1 and OsCPK17 (Ingram et al ., ; Almadanim et al ., ), or showed reduced activity compared to the calcium‐activated full‐length kinase (Asai et al ., ; Dubiella et al ., ). Ingram et al .…”
Section: Structure and Regulation Of Cdpks/crksmentioning
confidence: 99%
“…Upon binding of Ca 2+ to the EF-hands a dramatic structural rearrangement leads to a segmentation of the autoinhibitory helix around the calmodulin like-domain altering the interaction and relieving the inhibition [76]. A study with CDPK1 showed that upon binding calcium the CAD domain rotates with respect to the kinase domain and in addition to relieving autoinhibition stabilizes the active form of the enzyme [80]. The Toxoplasma CDPK1 is essential and conditional knockdown mutants of TgCDPK1 are defective in microneme secretion, motility, host-cell invasion and egress [48].…”
Section: Ca2+-dependent Protein Kinasesmentioning
confidence: 99%